ANALISIS EFEKTIFITAS GASTROPROTEKTIF EKSTRAK BAWANG MERAH (ALLIUM CEPA L) TERHADAP RATTUS NORVEGICUS YANG DI INDUKSI ASAM MEFENAMAT - Deinike Wanita Marwan; Fakhrun Nisya Zain; Ruswaldi Munir; Evy Eryta (Collaborative Medical Journal, 2024)
Acute or chronic inflammatory diseases of the gastric mucosa caused by exogenous and endogenous factors can cause symptoms of dyspepsia, these diseases are clinically visible endoscopically and require histological confirmation. According to the World Health Organization (WHO), the incidence of gastritis cases in the world is around 1.8 – 2.1 million of the total population each year, in Southeast Asia it is around 583,635 of the total population each year. Then gastritis is also caused by an imbalance of the aggressive factors HCl, pepsin, and gastric defense factors with the defensive factor, namely mucus bicarbonate. One of the causes of this imbalance of aggressive-defensive factors is the use of NSAIDs (non-steroidal anti-inflammatory drugs). This study aims to analyze the effectiveness of administering gastroprotective red onion extract to Rattus Norvegicus induced by mefenamic acid. With a true experimental method, a post test approach with control group. This study used 30 mice which were divided into 5 groups with 2 control groups and 3 treatment groups. Induction of mefenamic acid at a dose of 23.25 mg/head/day/sonde for 10 days. Then proceed with giving red onion extract for 10 days to each group. The research results showed that sample data was p = 0.001 (p<0.05) indicating that red onion extract (Allium Cepa L) had gastroprotective effectiveness in male white rats (Rattus Norvergicus). Research regarding the effectiveness of red onion extract (Alliem cepa L) as gastroprotective against male white rats (Rattus norvegicus) needs to be carried out with other compounds or due to other causal factors.